An Analysis of the Translation Methods of Edgar Allan Poe's Short Story 'The Tell-Tale Heart' Based on Newmark's Theory - Putri Yulitha, Noviyanti Dwianisa (Loquēla (Journal of Linguistics, Literature, and Education), 2024)
This research analyses the translation methods used by Harum Wibowo in translating Edgar Allan Poe's short story "The Tell-Tale Heart" based on Peter Newmark's translation theory. This research identifies and assesses the translation methods utilized and examines their alignment with Newmark's theory, including eight translation methods: word-for-word translation, literal translation, faithful translation, communicative translation, semantic translation, adaptation, and free translation. The research employs a descriptive qualitative method with content analysis techniques. The findings indicate that the translator tends to use communicative translation methods to maintain the horror nuances and Poe's distinctive language style. Additionally, some parts of the text show the use of modulation and transposition procedure to align with the target culture's context. This research is anticipated to enhance the understanding of the application of Newmark's theory in literary translation and assist translators in selecting appropriate methods to preserve the meaning and emotional impact of translated texts.